Loan loss provisions, non-performing loans and cost efficiency: evidence from Greece - Dadoukis, Aristeidis (2017)
This Thesis is a both timely and warranted examination of ‘risk management behaviour’ in Greek banking inter-linking cost efficiencies with loan loss provisioning practices during 2005 to 2012. Firstly, utilising Stochastic Frontier Analysis, we construct numerous cost efficiency frontiers and examine the evolution of cost efficiency in the banking system. Secondly, we investigate the risk management behaviour and the dominant loan loss provisioning practises in the domestic banking sector. These include capital management, efficiency hypotheses and the cyclicality of loan loss provisioning. Finally, we investigate the evolution of non-performing loans and if they are Granger caused by bad management or cost skimping within our construct of risk management behaviour. During 2005 to 2012 the ‘four core’ banks record strong performances and operate at higher levels of cost efficiency than their domestic competitors. This gap was reduced after the 2008 and 2010 financial crises, thus indicating an adverse impact due to the Private Sector Involvement. Overall, despite the so called bond haircut, the Greek banking system still recorded a strong performance where many banks operated close to the optimal efficiency levels, despite the ongoing deepening economic recession. In addition risk bank management behaviour presents loan loss provisioning practices that are counter cyclical to the Greek business cycle. These results suggest that banks have engaged in capital adjustment via their loan loss provisioning resources. In addition, we present evidence to support that low cost efficient banks reported higher levels of loan loss provisioning indicating difficulties in raising additional external capital. Finally, with respect to the development of non-performing loans we present evidence of cost skimping and little support concerning moral hazard in Greek bank risk management behaviour.